2014
DOI: 10.1111/1750-3841.12720
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Genetic Diversity, and Antibiotic Resistance of Bacillus cereus Isolated from Korean Fermented Soybean Products

Abstract: Bacillus cereus contamination is a major food safety problem for Korean fermented soybean products, but few studies have assessed its potential to cause foodborne illness. The objectives of this study were to investigate the prevalence and characteristics of B. cereus isolated from Korean fermented soybean products. B. cereus was detected in 110 of 162 (67.9%) samples. The highest B. cereus frequency was observed in deonjang (68 of 93 samples, 73.1%) and cheonggukjang (18 of 25, 72.0%); however, nonhemolytic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 29 publications
6
17
3
Order By: Relevance
“…In previous studies, the incidence ratios of B. cereus in doenjang samples varied considerably. As compared to the B. cereus detection rate in doenjang samples (52%) determined in this study, Kim et al (2015) reported that 73% of samples were contaminated with B. cereus from 93 doenjang samples, and Kim and Kim (2012) presented a much lower detection rate of 33.3% with contamination levels of 10 2 -10 5 cfu/g in doenjang samples. Yim et al (2015) also investigated 26 doenjang products and reported that 13 (50%) were contaminated with B. cereus.…”
Section: Prevalence Of B Cereus In Doenjangcontrasting
confidence: 48%
See 1 more Smart Citation
“…In previous studies, the incidence ratios of B. cereus in doenjang samples varied considerably. As compared to the B. cereus detection rate in doenjang samples (52%) determined in this study, Kim et al (2015) reported that 73% of samples were contaminated with B. cereus from 93 doenjang samples, and Kim and Kim (2012) presented a much lower detection rate of 33.3% with contamination levels of 10 2 -10 5 cfu/g in doenjang samples. Yim et al (2015) also investigated 26 doenjang products and reported that 13 (50%) were contaminated with B. cereus.…”
Section: Prevalence Of B Cereus In Doenjangcontrasting
confidence: 48%
“…Among the positive strains for NHE toxin, 83% (29 out of 35) produced high levels of the toxin (production at an index of 4). These proportions are relatively high compared to previous works which investigated NHE toxin production with the same kits in doenjang isolates (Kim et al, 2015) and foodrelated isolates (Chon, Kim, Lee, Hyeon, & Seo, 2012;Lee et al, 2012;Rahmati & Labbe, 2008). Of the 35 B. cereus isolates, 24 strains (69%) were negative for all 3 genes in the HBL complex (hblACD), and 8 isolates (23%) showed amplification products for 1 or 2 genes.…”
Section: Enterotoxin Production and Profiling Of Related Genesmentioning
confidence: 72%
“…On the other hand, all isolates show the highest level of susceptibility towards imipenem (100%), norfloxazin (100%), tobramycin (96.67%). The results were in close agreement to a study by Andrews and Wise (2002), Park et al (2009) and Kim et al (2015). It is not surprising since imipenem could be prescribed by doctors as a treatment for bacterial infection (Letchumanan et al, 2015).…”
Section: Antibiotic Resistancesupporting
confidence: 89%
“…All isolates were highly resistance to ß-lactam antibiotics penicillin (100%), and ampicillin (100%). High penicillin and ampicillin resistant were also observed in B. cereus in fermented soybean (Kim et al, 2015). Andrews and Wise (2002) and Park et al (2009) also reported that B. cereus were highly resistant to penicillin and ampicillin.…”
Section: Antibiotic Resistancementioning
confidence: 80%
“…The sensitivity of B. cereus to 20 antimicrobial agents was tested using the standard Kirby-Bauer disk diffusion method (Park et al, 2009; The Clinical and Laboratory Standards Institute [CLSI], 2010; Kim et al, 2015;Gao et al, 2018;Osman et al, 2018;Yu et al, 2019). The B. cereus isolates were streaked on the nutrition agar plate and grown 16-18 h at 37 • C. The colony was then picked and suspended using 0.85% physiological saline to 0.5 McFarland standard and spread on the surface of a Mueller-Hinton agar plate.…”
Section: Antimicrobial Susceptibility Testingmentioning
confidence: 99%